Linguistic Error in Writing Arabic on Students of Pondok Pesantren Al-Muhsinin Kerinci - Muhammad Fadhlan; Uril Bahruddin; Ahmad Fikri; Nur Yasin Shirotol Mustaqim; Abdul Muid (Abjadia, 2021)
Language competence of students when learning Arabic is very little noticed by Arabic language learners because it is very difficult for students to apply to what they learn from Arabic verbally and editorially. This study aims to describe the types of linguistic errors in Arabic writing and the reason for this error among Arabic learning in al-Muhsinin boarding schools. This study uses Henry Tarigan's qualitative error analysis method which consists of four stages: identifying errors, classification of errors, explaining errors, and evaluation of errors. This study also uses Miles and Huberman method in identifying the causes of the occurrence of error, namely: observation, interview, and documentation. The Documentation used in this studies is: student notebook in translate lessons (tarjamah), student notebook about holiday. The results of this study cover several aspects, namely grammatical errors, mistakes in choosing the right Arabic vocabulary, and cultural errors in writing Arabic in accordance with the grammar in Arabic. Linguistic errors obtained are as follows: students' mistakes determine nakirah and ma'rifah, ifrod, tas'niah and jamak, irob, kalimat azzaidah and kalimat an-naqisah. The errors in the selection of the right Arabic vocabulary are: 1) Using the word "Takrir ad-Dars" in the sentence repeating learning, 2) Using the word "Istagraqo" in time-consuming sentences. The causes of errors in writing Arabic are: students' ability to master Arabic vocabulary is very low, lack of governance in Arabic (Nahwu and Sharaf). From some of the results presented above can be an evaluation material for Arabic learners, especially in the learning of writing skills.